MENINGKATKAN EFIKASI DIRI DALAM PEMBUATAN KEPUTUSAN KARIER SISWA MELALUI TEKNIK MODELING SIMBOLIK - Setiawati, Rini (Universitas Borneo Tarakan, 2022)
Making career decisions for students is not an easy matter. Sometimes, students encounter obstacles and doubts before deciding on a career path. To overcome individual uncertainty in making career decisions, it is necessary to have self-efficacy. Student self-efficacy in making student career decisions needs to be grown and developed. The symbolic modeling technique as an alternative in increasing self-efficacy in making career decisions was tested for its effectiveness in this study. The quasi-experimental in this study divided the research subjects into two groups, namely control and experiment where each group consisted of 16 students. The control group was given conventional treatment by the BK teacher, while the experimental group received treatment in the form of symbolic modeling techniques. The self-efficacy scale in making career decisions for students of class X SMA N 1 Tempel, was tested by t-test to determine the effectiveness of symbolic modeling techniques. The result of the hypothesis test is that the t-count value is greater than the t-table which is -2.380 1.703. Based on the results of the t-test, it can be concluded that self-efficacy in career decision making can be improved through symbolic modeling techniques.Keywords: symbolic modeling, self-efficacy, career decision making